From the pathogenesis to the cure of indolent B-cell lymphoproliferative disorders associated with hepatitis C virus infection: which role for direct-acting antivirals?. Issue 8 (3rd August 2017) - Visentini, Marcella; Fiorilli, Massimo; Casato, Milvia
ABSTRACT: Introduction : Hepatitis C virus (HCV) causes monoclonal B cell lymphoproliferative disorders ranging from benign, such as in mixed cryoglobulinemia (MC), to indolent or aggressive lymphomas. MC and indolent lymphomas commonly regress when HCV is eradicated with interferon (IFN) therapy; however, sustained virologic response (SVR) to IFN is achieved only in ~50% of patients. The new all oral direct-acting antivirals (DAA), yielding nearly 100% SVR, promise a breakthrough in the treatment of HCV-associated lymphoproliferative disorders, but experience is still scanty. Areas covered : A literature search was performed to summarize current pathogenetic hypotheses in HCV-associated indolent lymphoproliferative disorders and to identify clinical trials focused on the use of antiviral therapy. Hematological outcomes of IFN-based and IFN-free DAA-based regimens were compared. Expert commentary : While MC appears to regress in most patients after DAA therapy, the still very limited experience with indolent lymphomas suggests that hematologic responses might be less than those observed with IFN. Furthermore, anecdotal observations of early progression to aggressive lymphoma after DAA are disquieting. Large studies are needed to determine the values and limits of DAA for treating HCV-associated indolent lymphomas and to identify subgroups at risk of non-response.